2000
DOI: 10.1063/1.1320844
|View full text |Cite
|
Sign up to set email alerts
|

Inverse scattering for near-field microscopy

Abstract: We derive the analytic singular value decomposition of the linearized scattering operator for scalar waves. This representation leads to a robust inversion formula for the inverse scattering problem in the near zone. Applications to near-field optics are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
75
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 14 publications
0
75
0
Order By: Relevance
“…Means to interpret NSOM images have been developed, 8,9 including the solution of a three-dimensional near-field inverse scattering problem. [10][11][12][13][14][15][16][17][18] The resulting methods are known as near-field optical tomography ͑NFOT͒. NFOT experiments require the acquisition of multiple complete NSOM data sets for varying directions of illumination or observation of the field.…”
mentioning
confidence: 99%
“…Means to interpret NSOM images have been developed, 8,9 including the solution of a three-dimensional near-field inverse scattering problem. [10][11][12][13][14][15][16][17][18] The resulting methods are known as near-field optical tomography ͑NFOT͒. NFOT experiments require the acquisition of multiple complete NSOM data sets for varying directions of illumination or observation of the field.…”
mentioning
confidence: 99%
“…It was recently demonstrated that when both the phase and amplitude of the optical near field are available, the near-field ISP may be solved, and an inversion formula was presented in [19]. Validation of the results was demonstrated by numerical simulation.…”
Section: Introductionmentioning
confidence: 97%
“…The linearized inverse problem has the solution = K ␣ + ⌽ ␣ , where K ␣ + denotes the pseudoinverse of K ␣ which has been obtained elsewhere. 2,6 To derive the solution to the nonlinear ISP, we act on Eq. ͑2͒ with K + and thereby obtain ͑6͒ where ˜͑ 1͒ = K ␣ + ⌽ ␣ .…”
Section: ͑3͒mentioning
confidence: 99%
“…This inverse scattering problem ͑ISP͒ has been studied within the accuracy of the single-scattering or first Born approximation. 6 The question of existence and uniqueness of solutions has been addressed, and computationally efficient inversion formulas are known. 2 The purpose of this letter is to extend these results to account for the effects of multiple scattering.…”
mentioning
confidence: 99%
See 1 more Smart Citation